2011
DOI: 10.3109/10428194.2011.607527
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue with fludarabine: effect on tumor microenvironment

Abstract: Gastric Helicobacter pylori (HP) positive extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT) develops during chronic antigenic stimulation with specific T-cell help. Chemotherapy that acts both on the malignant B-cells and on T-cells in the microenvironment, i.e. nucleoside analogs, might therefore be an attractive treatment. In 14 patients with gastric MALT lymphoma treated with fludarabine, alterations in T-cell subsets were studied in subsequent peripheral blood samples and in gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…However, unexpectedly, the number of CD3+ cells at the gastric tissue was not reduced at after treatment with fludarabine or bendamustine, even though these patients had intense lymphocytopenia in the peripheral blood (data not shown). Similar results were observed by de Boer et al [30]. Therefore, these observations highlights the fact that different type treatments influence T cells at peripheral blood and at gastric tissue in a very different way.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, unexpectedly, the number of CD3+ cells at the gastric tissue was not reduced at after treatment with fludarabine or bendamustine, even though these patients had intense lymphocytopenia in the peripheral blood (data not shown). Similar results were observed by de Boer et al [30]. Therefore, these observations highlights the fact that different type treatments influence T cells at peripheral blood and at gastric tissue in a very different way.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, depletion of T reg cells was slightly slower in patients treated with antibiotics than in those cases treated with purine analog structure drugs. In a recent published study in a similar population, an increase in density of FOXP3+ cells after treatment with oral fludarabine until a CR was documented [30]. With regard to CD3+ cells, we observed a modest reduction of these cells at gastric tissue after treatment with eradication therapy in responding cases.…”
Section: Discussionsupporting
confidence: 65%
“…In particular, Flu proved to be a potent inducer of Tregs when used to treat AML cells before in vitro cultures, whereas Eto has a weak capacity to induce Tregs, while maintaining T-cell stimulatory function. These results are not surprising, given the well-established immunosuppressive activity of Flu, especially in the context of lymphomas and chronic lymphocytic leukemia [62]. However, to our knowledge, this is the first demonstration that, when used to pulse DCs in T-cell cultures (cross-priming effect), Flu-treated AML cells may potently act as a Treg inducer, thus providing a new immunosuppressive mechanism associated with Flu administration.…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, de Boer et al reported a small series of translocation positive gastric MALT lymphoma patients treated with fludarabine, resulting in decrease in T cell subsets in peripheral blood samples and a significant increase in the amount of FOXP3+ T cells in gastric biopsy samples [38]. That increase was not observed in patients who were treated with H. pylori eradication therapy only.…”
Section: Combining Strategiesmentioning
confidence: 96%
“…That increase was not observed in patients who were treated with H. pylori eradication therapy only. They speculated that by modulating the balance of T cell subsets and their activation state via Tregs, treatment with fludarabine might restore the defect in perforin-mediated cytotoxicity and Fas-mediated apoptosis and contribute to the clearance of the malignant B cells [38].…”
Section: Combining Strategiesmentioning
confidence: 99%